2019
DOI: 10.1111/jfbc.12861
|View full text |Cite
|
Sign up to set email alerts
|

Rational combinations of indirubin and arylidene derivatives exhibit synergism in human non‐small cell lung carcinoma cells

Abstract: Rational combination of natural and synthetic derivatives to treat lung cancer has advantages of both efficacy and safety. Herein, the combination of indirubin‐3‐monoxime (I3M), a chemical derived from Chinese herbal medicine and FXY‐1, a synthetic arylidene derivative, was tested for combined activity in lung cancer cells. A dose‐dependent synergistic reduction in cell viability was recorded with the combinations in A549 and NCI‐H460 cells. Combination treatments of I3M and FXY‐1 showed antimetastatic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Cell proliferations were assessed using MTT assay as described elsewhere 16 . AML cells (5 × 10 3 cells/well) were grown in a 96-well tissue culture plate in regular growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…Cell proliferations were assessed using MTT assay as described elsewhere 16 . AML cells (5 × 10 3 cells/well) were grown in a 96-well tissue culture plate in regular growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA was performed according to the manufacturer's instructions. Cell proliferation was assessed using the MTT assay, as described previously [8]. Briefly, THP-1 and HL-60 cells at a concentration of 5 × 10 3 cells/well were grown in 96-well tissue culture plates in regular growth medium.…”
Section: Computational Docking Analysismentioning
confidence: 99%
“…Therefore, targeting ERs in AML cells could afford a reasonable target to combat disease progression. Tumor progression and hence is regarded as a valid target to control rapidly proliferating cancer cells [8]. Although AML is not directly linked to sex hormones, the relationship between estrogen, ERs, and AML has been documented [2].…”
Section: Introductionmentioning
confidence: 99%
“…This component has been documented for its therapeutic properties, such as antioxidant [9] and anti‐inflammatory [10]. It also effectuates against various forms of cancers, including colon [11], lung [12], kidney [10], and leukemia [13]. Some studies reported that Tq controls proliferating cancer cells through various signaling pathways, such as PIP3/Akt/NF‐κB [14], MAPK [15], and STAT‐3 [16].…”
Section: Introductionmentioning
confidence: 99%